2014
DOI: 10.21609/jiki.v7i1.252
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Twitter is a social media application, which can give a sign for identifying user emotion. Identification of user emotion can be utilized in commercial domain, health, politic, and security problems. The problem of emotion identification in twit is the unstructured short text messages which lead the difficulty to figure out main features. In this paper, we propose a new framework for identifying the tendency of user emotions using specific features, i.e. hashtag, emoji, emoticon, and adjective term. Preproces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As emoji are widely used in expressing emotions, they have become an effective means of sentiment analysis (Hogenboom et al, 2013; Cappallo et al, 2015). A number of studies have confirmed the effective performance of emoji in sentiment analysis (Sari et al, 2014; Cahyaningtyas et al, 2017; Felbo et al, 2017; LeCompte and Chen, 2017). Besides, emoji-based sentiment analysis is language-independent and exhibits cross-language validity (Guthier et al, 2017), for example, Al-Azani et al (2018) found that emoji can also be used in analyzing the sentiment of Arabic tweets.…”
Section: Research Fields Regarding Emojimentioning
confidence: 94%
“…As emoji are widely used in expressing emotions, they have become an effective means of sentiment analysis (Hogenboom et al, 2013; Cappallo et al, 2015). A number of studies have confirmed the effective performance of emoji in sentiment analysis (Sari et al, 2014; Cahyaningtyas et al, 2017; Felbo et al, 2017; LeCompte and Chen, 2017). Besides, emoji-based sentiment analysis is language-independent and exhibits cross-language validity (Guthier et al, 2017), for example, Al-Azani et al (2018) found that emoji can also be used in analyzing the sentiment of Arabic tweets.…”
Section: Research Fields Regarding Emojimentioning
confidence: 94%
“…Accordingly, they are utilized for research in various fields. Due to their function as emotional signals [6,7] adding a sentimental information to a written text, sentiment analysis or emotion identification is one application field within computer science [7,9,[12][13][14][15][16][17], which, among other things, led to the result that the utilization of emojis helps to improve sentiment scores [18,19]. Other research questions related to emojis are of semantic origin and explore their meaning and use [14,[20][21][22].…”
Section: State Of the Artmentioning
confidence: 99%